Examination of Cadmium Uptake of Rye-Grass (Lolium Perenne) in Small Pot Experiment - Szabó, Szilárd; Hangyel, László; Ágoston, Csaba (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
There is a relevant effect on soil properties on the plant uptake of heavy metals. The plants show different reaction on these kind of loadings. Some species extinct at a certain amount of heavy metal concentration and others just accumulate them without any kind of visible sign. In this paper a cadmium loading were carried out (5 mg/kg) with zinc addition (5 mg/kg) in a small pot experiment with rye-grass (Lolium perenne). Soil samples were taken from 4 sites from ploughland, grass land and forest land use types. It was compared the accumulation characteristics of the two metals and analysed their interconnection with the soil properties. It was detected that although, the difference between the zinc and cadmium load of the soils compared to the metal content of the soil is about 500 times (1/10 in the case of zinc and 50 times in the case of cadmium) the difference in the plant uptake is only 4–7 times. There is a close correlation between the zinc and cadmium uptake of plants and the cadmium concentration of soils plays an important role in it. Zinc shows positive correlation while cadmium exhibits negative correlation with organic matter. This can be explained by that zinc prefers fulvous acids when forming readily solvable chelats while cadmium bonds to more complexly polymerized humus material with longer carbon chain. Therefore zinc is solved even by root acids in contrast to cadmium that can be solved only by stronger acids. Besides organic colloids inorganic colloids i.e. clay fraction also showed close correlation.